Smart Education for Sustainable Future: Technology Integration in Achieving the 2030 SDGs in Indonesia - Ceceng Saepulmilah; Luqman Al-Hakim Musthafa; Tatang Muh Nasir; A. Heris Hermawan; Angga Yogaswara; Muhamad Yasir; Dadang Komara (Universitas Pendidikan Ganesha, 2025)
In the era of the Industrial Revolution 4.0, the integration of digital technology in education has become essential. Smart Education emerges as an ICT-based innovation to promote effective, flexible, and future-oriented learning. This study aims to analyze the role and implementation strategies of Smart Education in Indonesia in accelerating the achievement of the 2030 SDGs, particularly in improving education quality, expanding access, and strengthening digital literacy, using a quantitative survey design. A quantitative approach with a survey design was employed. Data were collected through a questionnaire developed based on Smart Education indicators, including digital infrastructure, human resource competence, policy and regulatory frameworks, as well as collaboration and innovation. Instrument validity and reliability were examined using item–total correlation analysis and Cronbach’s Alpha. The findings indicate that Smart Education contributes significantly to the acceleration of the 2030 SDGs, especially Goal 4 on quality education. More than seventy percent of respondents reported tangible benefits, including improved access to digital learning resources, increased learning flexibility, and greater time efficiency. Multiple linear regression analysis revealed that all examined factors had significant effects, with human resource competence showing the strongest correlation (r = 0.72). The study’s implications highlight the need to prioritize policies that strengthen digital competencies, ensure equitable technological infrastructure, and develop adaptive regulations to support sustainable, inclusive, and future-oriented Smart Education implementation.